Terra e universo : construção e validação de um teste de desempenho escolar em ciências - Ferreira, Joyce de Souza (2016)
This study aimed to construct and validate issues related to the thematic area "Earth and Universe", with the purpose of generating an assessment tool in Science, that allows to analyze the different levels of knowledge of students in the 9th grade of elementary school. Based on the Franzolin Cone Theory (2009), it was possible to develop a gradient passing high school, elementary school, elementary school II and Common Sense, in which we can analyze the approach and departure from the reference knowledge in each elaborate question. This is a documentary and exploratory research, with qualitative and quantitative approach. The steps of the research were divided into five: (i) Construction of a gradient based on Cone Theory Franzolin (2009); (Ii) Research subjects; (Iii) Construction and Validation of reference matrix; (Iv) Preparation of the issues; (V) validation of the issues. For data analysis, we used the SPSS (Statistical Package for Social Sciences). Among the analyzes relevant statistics, simple frequencies were carried out, the calculation of Cronbach's Alpha and made correlations Spearman rho. We conclude that it is feasible to build a school performance test that takes into account the plurality of ideas of students, as through the results was possible to observe the level of knowledge of students in relation to the contents of the axis 'Earth and the Universe'.